Skin Microbiota - Fifa Argentina; Rusmawardiana Rusmawardiana; Grady Garfendo (Fakultas Kedokteran Universitas Sriwijaya, 2020)
The skin is a complex and dynamic ecosystem. It may act as physical barrier to bar the invasion of foreign pathogens while concomitantly providing home to commensals bacteria, fungi and viruses. These microbes were known as microbiota. Over a human’s life span, skin cells, immune cells, and microbiota will integrate to maintain homeostasis of skin’s physiology and immune barrier, both under healthy conditions and also under stresses (infection and wounding). Shifts in the normal microbiota may cause diseases such as atopic dermatitis and psoriasis even though pathophysiology of these conditions is still unknown.